2023
DOI: 10.3390/s23031367
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Mental Workload Index Assessed by EEG with Different Electrode Configurations and Signal Pre-Processing Pipelines

Abstract: Background and Objective: Mental workload (MWL) is a relevant construct involved in all cognitively demanding activities, and its assessment is an important goal in many research fields. This paper aims at evaluating the reproducibility and sensitivity of MWL assessment from EEG signals considering the effects of different electrode configurations and pre-processing pipelines (PPPs). Methods: Thirteen young healthy adults were enrolled and were asked to perform 45 min of Simon’s task to elicit a cognitive dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The analysis of the cognitive aspects of mental workload in this study showed that at a noise level of 70 dB with a theta-to-alpha ratio value that increased from the noise level below, participants started mentioning how noise affected their mental workload. The results indicate a correlation between band ratios and mental workload stages, particularly between theta and alpha bands, aligning with the findings of [63,80]. Additionally, a study by [81] also justifies its potential theta-to-alpha ratio as an indicator of workload.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The analysis of the cognitive aspects of mental workload in this study showed that at a noise level of 70 dB with a theta-to-alpha ratio value that increased from the noise level below, participants started mentioning how noise affected their mental workload. The results indicate a correlation between band ratios and mental workload stages, particularly between theta and alpha bands, aligning with the findings of [63,80]. Additionally, a study by [81] also justifies its potential theta-to-alpha ratio as an indicator of workload.…”
Section: Discussionsupporting
confidence: 83%
“…Different cognitive states correspond to different indicators, some being controversial due to different experimental tasks [35,62]. In this study, after reviewing the relevant literature, three indicators were selected as cognitive performance measurement metrics, namely the cognitive aspects of attention measured based on the prefrontal beta signals of the AF3, AF4, F3, and F4 channels, stress aspects measured based on the alpha lateral frontal cortex signals of the F7 and F8 channels, and the mental workload aspects based on the theta/alpha ratios of the AF3, AF4, F3, F4, F7, F8, FC5, and FC6 channels [35,62,63].…”
Section: Eeg Recording and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the relevant thirteen studies, reproducibility was demonstrated for different electrode configurations and preprocessing pipelines (Mastropietro et al, 2023 ), for different settings of 2D and 3D environments (Kakkos et al, 2019 ), for a larger number of participants (Radüntz et al, 2020 ), for different tasks (Parekh et al, 2018 ; Boring et al, 2020 ; Sciaraffa et al, 2022 ), and over time (Gevins et al, 1998 ; Putze et al, 2013 ; Aricò et al, 2015 , 2016b ; Ortiz et al, 2020 ; Fox et al, 2022 ; Roy et al, 2022 ). Gevins et al ( 1998 ) also tested their findings on separate tasks to check cross-task performance and finally on data from a new participant to observe cross-subject performance.…”
Section: Reproducibility In Mental Workload Studies Using Eegmentioning
confidence: 99%
“…The paper “Reliability of Mental Workload Index Assessed by EEG with Different Electrode Configurations and Signal Pre-Processing Pipelines” [ 5 ] evaluates the reproducibility and sensitivity of mental workload assessment from EEG signals using different electrode configurations and pre-processing pipelines. The findings provide valuable insights into developing reliable methods for assessing cognitive tasks, crucial for enhancing human performance in various domains.…”
Section: Biomedical Sensors For Neurological and Rehabilitation Asses...mentioning
confidence: 99%